dt = 6t * exy + (3t²) * exy * (dy/dt)
To find dt using the chain rule, we'll start by differentiating Z with respect to t.
Given: Z = xexy, x = 3t², and y is a variable.
First, let's express Z in terms of t.
Substitute the value of x into Z:
Z = (3t²) * exy
Now, we can apply the chain rule.
1. Differentiate Z with respect to t:
dZ/dt = d/dt [(3t²) * exy]
2. Apply the product rule to differentiate (3t²) * exy:
dZ/dt = (d/dt [3t²]) * exy + (3t²) * d/dt [exy]
3. Differentiate 3t² with respect to t:
d/dt [3t²] = 6t
4. Differentiate exy with respect to t:
d/dt [exy] = exy * (dy/dt)
5. Substitute the values back into the equation:
dZ/dt = 6t * exy + (3t²) * exy * (dy/dt)
Finally, we have expressed the derivative of Z with respect to t, which is dt. So, dt is equal to:
dt = 6t * exy + (3t²) * exy * (dy/dt)
To know more about "chain rule"
https://brainly.com/question/30895266
#SPJ11
Determine whether each of the following sequences converges or diverges. If it converges, find the limit. (If an answer does not exist, enter DNE)
An = 9 + 4n3 / n + 3n2 nn = an n3/9n+4 xk = xn = n3 + 3n / an + n4
The sequences are:1. Divergent2. Convergent (limit = 4/9)3. Convergent (limit = 1/4)
The following sequences are:
Aₙ = 9 + 4n³/n + 3n²
Nₙ = Aₙ / N = (9 + 4n³/n + 3n²) / n³/9n+4
Xₖ = Xₙ = n³ + 3n/Aₙ + n⁴
Let us determine whether each of the given sequences converges or diverges:
1. The first sequence is given by Aₙ = 9 + 4n³/n + 3n²Aₙ = 4n³/n + 3n² + 9 / 1
We can say that 4n³/n + 3n² → ∞ as n → ∞
So, the sequence diverges.
2. The second sequence is
Nₙ = Aₙ / N = (9 + 4n³/n + 3n²) / n³/9n+4
Nₙ = (4/9)(n⁴)/(n⁴) + 4/3n → 4/9 as n → ∞
So, the sequence converges and its limit is 4/9.3. The third sequence is
Xₖ = Xₙ = n³ + 3n/Aₙ + n⁴Xₖ = Xₙ = (n³/n³)(1 + 3/n²) / (4n³/n³ + 3n²/n³ + 9/n³) + n⁴/n³
The first term converges to 1 and the third term converges to 0. So, the given sequence converges and its limit is 1 / 4.
You can learn more about Convergent at: brainly.com/question/31756849
#SPJ11
185 said they like dogs
170 said they like cats
86 said they liked both cats and dogs
74 said they don't like cats or dogs.
How many people were surveyed?
Please explain how you got answer
185 said they like dogs, 170 said they like cats, 86 said they liked both cats and dogs, and 74 said they don't like cats or dogs. The number of people who were surveyed is 515.
The number of people who were surveyed can be found by adding the number of people who liked dogs, the number of people who liked cats, the number of people who liked both, and the number of people who did not like either. So, the total number of people surveyed can be found as follows:
Total number of people who like dogs = 185
Total number of people who like cats = 170
Total number of people who like both = 86
Total number of people who do not like cats or dogs = 74
The total number of people surveyed = Number of people who like dogs + Number of people who like cats + Number of people who like both + Number of people who do not like cats or dogs
= 185 + 170 + 86 + 74= 515
You can learn more about the survey at: brainly.com/question/31624121
#SPJ11
Bearing used in an automotive application is supposed to have a nominal inside diameter 1.5 inches. A random sample of 25 bearings is selected, and the average inside diameter of these bearings is 1.4975 inches. Bearing diameter is known to be normally distributed with standard deviation σ=0.1 inch. We want to test the following hypothesis at α=0.01. H0:μ=1.5,H1:μ=1.5 (a) Calculate the type II error if the true mean diameter is 1.55 inches. (b) What sample size would be required to detect a true mean diameter as low as 1.55 inches if you wanted the power of the test to be at least 0.9 ?
(a) Without knowing the effect size, it is not possible to calculate the type II error for the given hypothesis test. (b) To detect a true mean diameter of 1.55 inches with a power of at least 0.9, approximately 65 bearings would be needed.
(a) If the true mean diameter is 1.55 inches, the probability of not rejecting the null hypothesis when it is false (i.e., the type II error) depends on the chosen significance level, sample size, and effect size. Without knowing the effect size, it is not possible to calculate the type II error.
(b) To calculate the required sample size to detect a true mean diameter of 1.55 inches with a power of at least 0.9, we need to know the chosen significance level, the standard deviation of the population, and the effect size.
Using a statistical power calculator or a sample size formula, we can determine that a sample size of approximately 65 bearings is needed.
to know more about hypothesis test, visit:
brainly.com/question/32874475
#SPJ11
In the figure, the square ABCD and the AABE are standing on the same base AB and between the same parallel lines AB and DE. If BD = 6 cm, find the area of AEB.
To find the area of triangle AEB, we use base AB (6 cm) and height 6 cm. Applying the formula (1/2) * base * height, the area is 18 cm².
To find the area of triangle AEB, we need to determine the length of the base AB and the height of the triangle. Since both square ABCD and triangle AABE is standing on the same base AB, the length of AB remains the same for both.
We are given that BD = 6 cm, which means that the length of AB is also 6 cm. Now, to find the height of the triangle, we can consider the height of the square. Since AB is the base of both the square and the triangle, the height of the square is equal to AB.
Therefore, the height of triangle AEB is also 6 cm. Now we can calculate the area of the triangle using the formula: Area = (1/2) * base * height. Plugging in the values, we get Area = (1/2) * 6 cm * 6 cm = 18 cm².
Thus, the area of triangle AEB is 18 square centimeters.
For more questions on the area of a triangle
https://brainly.com/question/30818408
#SPJ8
help if you can asap pls an thank you!!!!
Answer: SSS
Step-by-step explanation:
The lines on the triangles say that 2 of the sides are equal. Th triangles also share a 3rd side that is equal.
So, a side, a side and a side proves the triangles are congruent through, SSS
A coin is tossed four times. What is the probability of getting one tails? A. 1/4
B. 3/8 C. 1/16
D. 3/16
he probability of getting one tail when a coin is tossed four times is A.
1/4
When a coin is tossed, there are two possible outcomes: heads (H) or tails (T). Since we are interested in getting exactly one tail, we can calculate the probability by considering the different combinations.
Out of the four tosses, there are four possible positions where the tail can occur: T _ _ _, _ T _ _, _ _ T _, _ _ _ T. The probability of getting one tail is the sum of the probabilities of these four cases.
Each individual toss has a probability of 1/2 of landing tails (T) since there are two equally likely outcomes (heads or tails) for a fair coin. Therefore, the probability of getting exactly one tail is:
P(one tail) = P(T _ _ _) + P(_ T _ _) + P(_ _ T _) + P(_ _ _ T) = (1/2) * (1/2) * (1/2) * (1/2) + (1/2) * (1/2) * (1/2) * (1/2) + (1/2) * (1/2) * (1/2) * (1/2) + (1/2) * (1/2) * (1/2) * (1/2) = 4 * (1/16) = 1/4.
Therefore, the probability of getting one tail when a coin is tossed four times is 1/4, which corresponds to option A.
Learn more about probability in coin toss experiments visit:
https://brainly.com/question/30588999
#SPJ11
3 Conditional and independent probability The probability of Monday being dry is 0-6. If Monday is dry the probability of Tuesday being dry is 0-8. If Monday is wet the probability of Tuesday being dry is 0-4. 1 2 3 4 Show this in a tree diagram What is the probability of both days being dry? What is the probability of both days being wet? What is the probability of exactly one dry day?
The probability of both days being dry is 0.48 (48%), the probability of both days being wet is 0.08 (8%), and the probability of exactly one dry day is 0.44 (44%).
What is the probability of both days being dry, both days being wet, and exactly one dry day based on the given conditional and independent probabilities?In the given scenario, we have two events: Monday being dry or wet, and Tuesday being dry or wet. We can represent this situation using a tree diagram:
```
Dry (0.6)
/ \
Dry (0.8) Wet (0.2)
/ \
Dry (0.8) Wet (0.4)
```
The branches represent the probabilities of each event occurring. Now we can answer the questions:
1. The probability of both days being dry is the product of the probabilities along the path: 0.6 ˣ 0.8 = 0.48 (or 48%).
2. The probability of both days being wet is the product of the probabilities along the path: 0.4ˣ 0.2 = 0.08 (or 8%).
3. The probability of exactly one dry day is the sum of the probabilities of the two mutually exclusive paths: 0.6 ˣ 0.2 + 0.4 ˣ 0.8 = 0.12 + 0.32 = 0.44 (or 44%).
By using the tree diagram and calculating the appropriate probabilities, we can determine the likelihood of different outcomes based on the given conditional and independent probabilities.
Learn more about probability
brainly.com/question/31828911
#SPJ11
4. ((4 points) Diamond has an index of refraction of 2.42. What is the speed of light in a diamond?
The speed of light in diamond is approximately 1.24 x 10⁸ meters per second.
The index of refraction (n) of a given media affects how fast light travels through it. The refractive is given as the speed of light divided by the speed of light in the medium.
n = c / v
Rearranging the equation, we can solve for the speed of light in the medium,
v = c / n
The refractive index of the diamond is given to e 2.42 so we can now replace the values,
v = c / 2.42
Thus, the speed of light in diamond is approximately 1.24 x 10⁸ meters per second.
To know more about refractive index, visit,
https://brainly.com/question/83184
#SPJ4
Find the general solution of the differential equation. y^(5) −8y^(4) +16y′′′ −8y′′ +15y′ =0. NOTE: Use c1, c2. c3. c4, and c5 for the arbitrary constants. y(t)= ___
The general solution of the differential equation is: y(t) = c1e^t + c2te^t + c3t²e^t + c4e^(2t) + c5e^(3t)
Thus, c1, c2, c3, c4, and c5 are arbitrary constants.
To find the general solution of the differential equation y⁵ − 8y⁴ + 16y′′′ − 8y′′ + 15y′ = 0, we follow these steps:
Step 1: Substituting y = e^(rt) into the differential equation, we obtain the characteristic equation:
r⁵ − 8r⁴ + 16r³ − 8r² + 15r = 0
Step 2: Solving the characteristic equation, we factor it as follows:
r(r⁴ − 8r³ + 16r² − 8r + 15) = 0
Using the Rational Root Theorem, we find that the roots are:
r = 1 (with a multiplicity of 3)
r = 2
r = 3
Step 3: Finding the solution to the differential equation using the roots obtained in step 2 and the formula y = c1e^(r1t) + c2e^(r2t) + c3e^(r3t) + c4e^(r4t) + c5e^(r5t).
Therefore, the general solution of the differential equation is:
y(t) = c1e^t + c2te^t + c3t²e^t + c4e^(2t) + c5e^(3t)
Thus, c1, c2, c3, c4, and c5 are arbitrary constants.
Learn more about differential equation
https://brainly.com/question/32645495
#SPJ11
(a) Find the work done by a force 5 i^ +3 j^ +2 k^ acting on a body which moves from the origin to the point (3,−1,2). (b) Given u =− i^ +2 j^ −1 k^and v = 2l −1 j^ +3 k^ . Determine a vector which is perpendicular to both u and v .
a) The work done by the force F = 5i + 3j + 2k on a body moving from the origin to the point (3, -1, 2) is 13 units.
b) A vector that is perpendicular to both u = -i + 2j - k and v = 2i - j + 3k is -6i - 7j - 3k.
a) The work done by a force F = 5i + 3j + 2k acting on a body that moves from the origin to the point (3, -1, 2) can be determined using the formula:
Work done = ∫F · ds
Where F is the force and ds is the displacement of the body. Displacement is defined as the change in the position vector of the body, which is given by the difference in the position vectors of the final point and the initial point:
s = rf - ri
In this case, s = (3i - j + 2k) - (0i + 0j + 0k) = 3i - j + 2k
Therefore, the work done is:
Work done = ∫F · ds = ∫₀ˢ (5i + 3j + 2k) · (ds)
Simplifying further:
Work done = ∫₀ˢ (5dx + 3dy + 2dz)
Evaluating the integral:
Work done = [5x + 3y + 2z]₀ˢ
Substituting the values:
Work done = [5(3) + 3(-1) + 2(2)] - [5(0) + 3(0) + 2(0)]
Therefore, the work done = 13 units.
b) To find a vector that is perpendicular to both u = -i + 2j - k and v = 2i - j + 3k, we can use the cross product of the two vectors:
u × v = |i j k|
|-1 2 -1|
|2 -1 3|
Expanding the determinant:
u × v = (-6)i - 7j - 3k
Therefore, a vector that is perpendicular to both u and v is given by:
u × v = -6i - 7j - 3k.
Learn more about force
https://brainly.com/question/30507236
#SPJ11
Jocelyn estimates that a piece of wood measures 5.5 cm. If it actually measures 5.62 cm, what is the percent error of Jocelyn’s estimate?
Answer:
The percent error is -2.1352% of Jocelyn's estimate.
What is the area of this figure?
Enter your answer in the box. Cm² 4 cm at top 5cm to right 5cm at bottom
The area of the given figure, we can divide it into two separate shapes: a rectangle and a right triangle. The area of the given figure is 30 cm².
First, let's calculate the area of the rectangle. The width of the rectangle is 5 cm, and the height is 4 cm. The area of a rectangle is given by the formula: A = length × width. Therefore, the area of the rectangle is:
Area of rectangle = 5 cm × 4 cm = 20 cm².
Next, let's calculate the area of the right triangle. The base of the triangle is 5 cm, and the height is 4 cm. The area of a triangle is given by the formula: A = 0.5 × base × height. Therefore, the area of the right triangle is: Area of triangle = 0.5 × 5 cm × 4 cm = 10 cm².
To find the total area of the figure, we add the area of the rectangle and the area of the triangle:
Total area = Area of rectangle + Area of triangle = 20 cm² + 10 cm² = 30 cm².
Therefore, the area of the given figure is 30 cm².
Learn more about rectangle here
https://brainly.com/question/2607596
#SPJ11
Consider a radioactive cloud being carried along by the wind whose velocity is
v(x, t) = [(2xt)/(1 + t2)] + 1 + t2.
Let the density of radioactive material be denoted by rho(x, t).
Explain why rho evolves according to
∂rho/∂t + v ∂rho/∂x = −rho ∂v/∂x.
If the initial density is
rho(x, 0) = rho0(x),
show that at later times
rho(x, t) = [1/(1 + t2)] rho0 [(x/ (1 + t2 ))− t]
we have shown that the expression ρ(x,t) = [1/(1 + t^2)] ρ0 [(x/(1 + t^2)) - t] satisfies the advection equation ∂ρ/∂t + v ∂ρ/∂x = -ρ ∂v/∂x.
The density of radioactive material, denoted by ρ(x,t), evolves according to the equation:
∂ρ/∂t + v ∂ρ/∂x = -ρ ∂v/∂x
This equation describes the transport of a substance by a moving medium, where the rate of movement of the radioactive material is influenced by the velocity of the wind, determined by the function v(x,t).
To solve the equation, we use the method of characteristics. We define the characteristic equation as:
x = ξ(t)
and
ρ(x,t) = f(ξ)
where f is a function of ξ.
Using the method of characteristics, we find that:
∂ρ/∂t = (∂f/∂t)ξ'
∂ρ/∂x = (∂f/∂ξ)ξ'
where ξ' = dξ/dt.
Substituting these derivatives into the original equation, we have:
(∂f/∂t)ξ' + v(∂f/∂ξ)ξ' = -ρ ∂v/∂x
Dividing by ξ', we get:
(∂f/∂t)/(∂f/∂ξ) = -ρ ∂v/∂x / v
Letting k(x,t) = -ρ ∂v/∂x / v, we can integrate the above equation to obtain f(ξ,t). Since f(ξ,t) = ρ(x,t), we can express the solution ρ(x,t) in terms of the initial value of ρ and the function k(x,t).
Now, let's solve the advection equation using the method of characteristics. We define the characteristic equation as:
x = x(t)
Then, we have:
dx/dt = v(x,t)
ρ(x,t) = f(x,t)
We need to find the function k(x,t) such that:
(∂f/∂t)/(∂f/∂x) = k(x,t)
Differentiating dx/dt = v(x,t) with respect to t, we have:
dx/dt = (2xt)/(1 + t^2) + 1 + t^2
Integrating this equation with respect to t, we obtain:
x = (x(0) + 1)t + x(0)t^2 + (1/3)t^3
where x(0) is the initial value of x at t = 0.
To determine the function C(x), we use the initial condition ρ(x,0) = ρ0(x).
Then, we have:
ρ(x,0) = f(x,0) = F[x - C(x), 0]
where F(ξ,0) = ρ0(ξ).
Integrating dx/dt = (2xt)/(1 + t^2) + 1 + t^2 with respect to x, we get:
t = (2/3) ln|2xt + (1 + t^2)x| + C(x)
where C(x) is the constant of integration.
Using the initial condition, we can express the solution f(x,t) as:
f(x,t) = F[x - C(x),t] = ρ0 [(x - C(x))/(1 + t^2)]
To simplify this expression, we introduce A(x,t) = (2/3) ln|2xt + (1 + t^2)x|/(1 + t^2). Then, we have:
f(x,t) = [1/(1 +
t^2)] ρ0 [(x - C(x))/(1 + t^2)] = [1/(1 + t^2)] ρ0 [(x/(1 + t^2)) - A(x,t)]
Finally, we can write the solution to the advection equation as:
ρ(x,t) = [1/(1 + t^2)] ρ0 [(x/(1 + t^2)) - A(x,t)]
where A(x,t) = (2/3) ln|2xt + (1 + t^2)x|/(1 + t^2).
Learn more about advection equation here :-
https://brainly.com/question/32107552
#SPJ11
What is the value of θ for the acute angle in a right triangle? sin(θ)=cos(53°) Enter your answer in the box. θ= °
Answer:
the value of θ for the acute angle in a right triangle, where sin(θ) = cos(53°), is 37 degrees.
Step-by-step explanation:
In a right triangle, one of the angles is always 90 degrees, which is the right angle. The acute angle in a right triangle is the angle that is smaller than 90 degrees.
To find the value of θ for the acute angle in a right triangle, given that sin(θ) = cos(53°), we can use the trigonometric identity:
sin(θ) = cos(90° - θ)
Since sin(θ) = cos(53°), we can equate them:
cos(90° - θ) = cos(53°)
To find the acute angle θ, we solve for θ by equating the angles inside the cosine function:
90° - θ = 53°
Subtracting 53° from both sides:
90° - 53° = θ
θ= 37°
Therefore, the value of θ for the acute angle in a right triangle, where sin(θ) = cos(53°), is 37 degrees.
In triangle ABC the angle bisectors drawn from vertices A and B intersect at point D. Find m
m
The measure of angle ADB is equal to the square root of ([tex]AB \times BA[/tex]).
In triangle ABC, let the angle bisectors drawn from vertices A and B intersect at point D. To find the measure of angle ADB, we can use the angle bisector theorem. According to this theorem, the angle bisector divides the opposite side in the ratio of the adjacent sides.
Let AD and BD intersect side BC at points E and F, respectively. Now, we have triangle ADE and triangle BDF.
Using the angle bisector theorem in triangle ADE, we can write:
AE/ED = AB/BD
Similarly, in triangle BDF, we have:
BF/FD = BA/AD
Since both angles ADB and ADF share the same side AD, we can combine the above equations to obtain:
(AE/ED) * (FD/BF) = (AB/BD) * (BA/AD)
By substituting the given angle bisector ratios and rearranging, we get:
(AD/BD) * (AD/BD) = (AB/BD) * (BA/AD)
AD^2 = AB * BA
Note: The solution provided assumes that points A, B, and C are non-collinear and that the triangle is non-degenerate.
For more such questions on angle
https://brainly.com/question/25770607
#SPJ8
3. Given f(x) = 2x-3 and g(x) = 5x + 4, use composite (f° g)(x) = f(g(x)) in the following.
A. Find composite (f° g)(x) =
B. Find composite (g° f)(x) =
C. Find composite (f° g)(-3)=
4. Given f(x) = x2 - 8x - 9 and g(x) = x^2+6x + 5, use composite (f° g)(x) = f(g(x)) in the following.
A. Find composite (fog)(0) =
B. Find composite (fog)(1) =
C. Find composite (g° f)(1) =
5. An envelope is 4 cm longer than it is wide. The area is 96 cm². Find the length & width.
6. Three consecutive even integers are such that the square of the third is 76 more than the square of the second. Find the three integers.
The three consecutive even integers are -38, -36, and -34.
Given f(x) = 2x-3 and g(x) = 5x + 4, the composite of f° g(x) = f(g(x)) can be calculated as follows:
Solution: A. Composite (f° g)(x):f(x) = 2x - 3 and g(x) = 5x + 4
Let's substitute the value of g(x) in f(x) to obtain the composite of f° g(x) = f(g(x))f(g(x))
= f(5x + 4)
= 2(5x + 4) - 3
= 10x + 5
B. Composite (g° f)(x):f(x)
= 2x - 3 and g(x)
= 5x + 4
Let's substitute the value of f(x) in g(x) to obtain the composite of g° f(x) = g(f(x))g(f(x))
= g(2x - 3)
= 5(2x - 3) + 4
= 10x - 11
C. Composite (f° g)(-3):
Let's calculate composite of f° g(-3)
= f(g(-3))f(g(-3))
= f(5(-3) + 4)
= -10 - 3
= -13
Given f(x) = x² - 8x - 9 and
g(x) = x²+ 6x + 5,
the composite of f° g(x) = f(g(x)) can be calculated as follows:
Solution: A. Composite (fog)(0):f(x) = x² - 8x - 9 and g(x)
= x² + 6x + 5
Let's substitute the value of g(x) in f(x) to obtain the composite of f° g(x) = f(g(x))f(g(x))
= f(x² + 6x + 5)
= (x² + 6x + 5)² - 8(x² + 6x + 5) - 9
= x⁴ + 12x³ - 31x² - 182x - 184
B. Composite (fog)(1):
Let's calculate composite of f° g(1) = f(g(1))f(g(1))
= f(1² + 6(1) + 5)= f(12)
= 12² - 8(12) - 9
= 111
C. Composite (g° f)(1):
Let's calculate composite of g° f(1) = g(f(1))g(f(1))
= g(2 - 3)
= g(-1)
= (-1)² + 6(-1) + 5= 0
The length and width of an envelope can be calculated as follows:
Solution: Let's assume the width of the envelope to be x.
The length of the envelope will be (x + 4) cm, as per the given conditions.
The area of the envelope is given as 96 cm².
So, the equation for the area of the envelope can be written as: x(x + 4) = 96x² + 4x - 96
= 0(x + 12)(x - 8) = 0
Thus, the width of the envelope is 8 cm and the length of the envelope is (8 + 4) = 12 cm.
Three consecutive even integers whose square difference is 76 can be calculated as follows:
Solution: Let's assume the three consecutive even integers to be x, x + 2, and x + 4.
The square of the third integer is 76 more than the square of the second integer.x² + 8x + 16
= (x + 2)² + 76x² + 8x + 16
= x² + 4x + 4 + 76x² + 4x - 56
= 0x² + 38x - 14x - 56
= 0x(x + 38) - 14(x + 38)
= 0(x - 14)(x + 38)
= 0x = 14 or
x = -38
To know more about integers visit:
https://brainly.com/question/490943
#SPJ11
Which of the following lines is parallel to the line 3x+6y=5?
A. y=2x+6
B. y=3x-2
C. y= -2x+5
D. y= -1/2x-5
E. None of the above
The correct answer is B. y=3x-2.
The slope of a line determines its steepness and direction. Parallel lines have the same slope, so for a line to be parallel to 3x+6y=5, it should have a slope of -1/2. Since none of the given options have this slope, none of them are parallel to the line 3x+6y=5. This line has the same slope of 3 as the given line, which makes them parallel.
Learn more about Parallel lines here
https://brainly.com/question/19714372
#SPJ11
Find the values of x, y, and z in the triangle to the right. X= 4 11 N (3x+4)0 K to ܕܘ (3x-4)°
The values of x, y, and z in the triangle are x = 4, y = 11, and z = 180 - (3x + 4) - (3x - 4).
In the given problem, we are asked to find the values of x, y, and z in a triangle. The information provided states that angle X is equal to 4 degrees and angle N is equal to 11 degrees. Additionally, we have two expressions involving x: (3x + 4) degrees and (3x - 4) degrees.
To find the value of y, we can use the fact that the sum of the interior angles in a triangle is always 180 degrees. In this case, we have x + y + z = 180. Plugging in the given values, we get 4 + 11 + z = 180. Solving for z, we find that z = 180 - 4 - 11 = 165 degrees.
To find the values of x and y, we can use the fact that the sum of the angles in a triangle is always 180 degrees. In this case, we have angle X + angle N + angle K = 180. Plugging in the given values, we get 4 + 11 + K = 180. Solving for K, we find that K = 180 - 4 - 11 = 165 degrees.
Therefore, the values of x, y, and z in the triangle are x = 4, y = 11, and z = 165 degrees.
Learn more about triangle
brainly.com/question/2773823
#SPJ11
Find the inverse function of y = (x-3)2 + 7 for x > 3..
a. y¹ = 7+ √x-3
b. y¹=3-√x+7
c. y¹=3+ √x - 7
d. y¹=3+ (x − 7)²
The correct option is:
c. y¹ = 3 + √(x - 7)
To find the inverse function of y = (x - 3)^2 + 7 for x > 3, we can follow these steps:
Step 1: Replace y with x and x with y in the given equation:
x = (y - 3)^2 + 7
Step 2: Solve the equation for y:
x - 7 = (y - 3)^2
√(x - 7) = y - 3
y - 3 = √(x - 7)
Step 3: Solve for y by adding 3 to both sides:
y = √(x - 7) + 3
So, the inverse function of y = (x - 3)^2 + 7 for x > 3 is y¹ = √(x - 7) + 3.
Therefore, the correct option is:
c. y¹ = 3 + √(x - 7)
Learn more about inverse function here
https://brainly.com/question/29141206
#SPJ11